3D Catalogue based on Augmented Reality in Android Operating System - Chandra Natalia; Purnomo Fredy; Ricky Michael Yoseph; Leonard Christianto; Verdian Arvin; Hendrick (MATEC Web of Conferences, 2016)
Along with the continued development of Smartphone and the era of globalization, human needs are increasing for technology. They continue to look for ways that can ease their lives and it is up to the explanation of the visualization that closer to the actual visualization and support fast, precise and clear retrieval of interactive information. In order to realize the visualization, augmented reality technology is being used. Augmented reality is a technology that uses camera technology to recognize real world, images, objects, and environments and superimposes virtual information and data onto reality in real time. It combines a virtual object into two or three dimensions in a real three-dimensional environment. By developing an application with augmented reality, it can help user to look more detail into a product and give advantages to company to save the brochure production cost. The development of this application is using client-side and server-side, where the client-side will be run on android smartphone and server-side using a php based web service. The goal of this paper is to develop a 3D catalogue that helps to depict a product in interactive ways with zoom, rotate, choose color, and animation features.